Bioaerogéis de nanocelulose e alginato enxertados com extrato de Maclura tinctoria - Coldebella, Rodrigo (2020)
The meaningful changes in the consumption pattern of modern society, allied with the pursuit for products made with sustainable raw materials, lead to economical and market opportunities providing environmental and social benefits. Thus, biodegradable products enable coherent, effective and concrete solutions in replacing fossil resources. The intend is then, to change the current economic model - extract, transform and dispose - eliminating or making the most of waste, keeping it in use and, when there is a need for disposal, so that this wastes can return to the environment as nutrients. We describe here a series of aerogels, biobased on nanocellulose and alginate, with potential use for absorbent and hemostatic dressings to be used in dental surgical procedures. Bioaerogels are porous and almost weightless materials, resulted from the replacement of the gel solvent by air, through various drying processes. The relative mechanical strength and its 3D nanostructured network suggest that aerogels can be used in processes that require exudate absorption. The biofunctionalization was achieved by immobilizing the extract of Maclura tinctoria in the aerogel structures. The antibacterial, antioxidant activities, the percentage of inhibition and the water absorption capacity suggest that these aerogels can be used as fluid absorbers, in the initial process of gingival healing, protecting the tooth socket and combating possible bacterial infections. Using less polutting products with low environmental impact and because of their biobased origin, aerogels are biodegradable at the end of their life cycle. We can mention at least three highlights obtained in this research: I) the creation of a biodegradable product derived from sustainable raw materials, replacing the collagen foams of porcine origin. II) the use of a natural biocide that can be an alternative to silver, and III) innovation inspired by nature and popular medicine. This work presents an innovative method to biofunctionalize aerogels, so that the load of the active component acts on its entire structure and not just superficially. Potentially, the method used can be reproduced and functionalized with other active products of organic origin. Although the characteristics obtained are highly relevant for the application in the pharmaceutical industry, complementary studies such as extract biofunctionalization tests and the optimization of formulations could provide relevant information for the feasible utilization of the produced materials.